1997
DOI: 10.1126/science.276.5312.593
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Auditory Cortex During Silent Lipreading

Abstract: Watching a speaker's lips during face-to-face conversation (lipreading) markedly improves speech perception, particularly in noisy conditions. With functional magnetic resonance imaging it was found that these linguistic visual cues are sufficient to activate auditory cortex in normal hearing individuals in the absence of auditory speech sounds. Two further experiments suggest that these auditory cortical areas are not engaged when an individual is viewing nonlinguistic facial movements but appear to be activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
601
4
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(665 citation statements)
references
References 21 publications
57
601
4
3
Order By: Relevance
“…Specifically, we argue that previously identified area Spt, which had been characterized as an auditory-motor integration area, might instead be considered a sensorymotor integration area for the vocal tract action system, much like the lateral intraparietal sulcus (area LIP) is a sensory-motor integration area for eye movements, and anterior intraparietal sulcus (area AIP) is a sensory-motor integration area for grasping (Culham, 2004;Grefkes et al, 2004). The fact that the planum temporale region activates to non-auditory stimulation (e.g., during silent lip reading (Calvert et al, 1997)) is consistent with this characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we argue that previously identified area Spt, which had been characterized as an auditory-motor integration area, might instead be considered a sensorymotor integration area for the vocal tract action system, much like the lateral intraparietal sulcus (area LIP) is a sensory-motor integration area for eye movements, and anterior intraparietal sulcus (area AIP) is a sensory-motor integration area for grasping (Culham, 2004;Grefkes et al, 2004). The fact that the planum temporale region activates to non-auditory stimulation (e.g., during silent lip reading (Calvert et al, 1997)) is consistent with this characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Boatman et al (1997) have reported in five patients that the stimulation of one temporal electrode in this region elicited a deficit in syllable discrimination. The more posterior part of the temporal region is also activated when phonological representations are accessed through devices other than auditory input, such as lip reading (Calvert and Campbell, 2003;Calvert et al, 1997), word generation (Buchsbaum et al, 2001;Wise et al, 2001), sign language processing (Petitto et al, 2000), and reading (Paulesu et al, 2000(Paulesu et al, , 2001. It is possible that top-down attention amplifies those speech representation, thus bringing knowledge of the characteristics of a human voice to supplement the poverty of the sinewave input and integrate its acoustical features into phonemic representations.…”
Section: Fmrimentioning
confidence: 99%
“…Klucharev, Mottonen, & Sams, 2003;Lebib et al, 2004). However, there is accumulating evidence that multimodal integration also includes the modulation of activity at cortical brain sites that used to be considered modality specific and are usually related to perceptual aspects of processing (Calvert et al, 1997(Calvert et al, , 1999. Most studies in subjects with ASD used audio-visual stimuli that implicated higher level (more cognitive) processing, like in the studies on speech and emotion processing (de Gelder et al, 1991;Hall et al, 2003).…”
mentioning
confidence: 99%